Content-Marketing-Strategien in der Unternehmenspraxis: Eine empirische Analyse - Hans-Christian Riekhof; Teresa Jacobi (PFH Private Hochschule Göttingen, 2016)
Although there is currently limited empirical research available on content marketing this topic is discussed quite intensively among marketing experts. Some of these even see a new paradigm on the rise because marketing strategies based on content are fundamentally different from traditional approaches where selling products and directly influencing customers and prospects are the dominating focus of marketing activities. In this paper, content marketing is used as the more generic term whereas native advertising, branded content, branded media or corporate journalism emphasize more particular aspects. [...]
Keywords: 330